Revenue Forecast and Public Expenditure Budget in a Mexican Municipality - Zúñiga-Espinoza, Nicolás Guadalupe; Reyna Parra, Alfonso (Technium Social Sciences Journal, 2025)
This review of budgeted revenue and public expenditure figures for the municipality of Culiacan, Sinaloa, Mexico, through the different revenue collection and expenditure implementation instruments corresponding to the 2023-2024 biennium, specifically analyzes comparative figures of the public resources to be exercised by governmental authorities. Collecting local revenues and deciding how to spend those resources has its benefits as well as consequences. Therefore, this paper proposes indicators for the public management of the budget of this municipality in northwestern Mexico.